Thermodynamic analysis of annual operation of a 370 MW power unit operating in CHP-mode. (5th August 2016) - Bartnik, Ryszard; Buryn, Zbigniew; Hnydiuk-Stefan, Anna
Highlights: Modeling of power unit adopted to cogeneration. Thermodynamic analysis of quasi-unsteady operation in the power system. Operating in CHP mode increase the overall effectiveness. Cogeneration leads to the accumulated savings in the use of the primary fuel. Cogeneration leads to the accumulated reduction of total pollution. Abstract: This paper presents a selection of the results of thermodynamic calculation of quasi-nonstationary annual operation of a power unit in a coal-fired power plant working in cogeneration. The results of calculations are summarized for the annual, actual mean-hourly course of the course of electrical capacity in the unit in accordance with its operation in the system of power and frequency regulation imposed by the Polish Power System. Concurrently, the results also take into account the annual demand for heat for the purposes of district heating, which is associated with the actual mean-hourly ambient temperature fluctuations overlapping with the electricity production.